Basalt fibre laminates non-destructively inspected after low-velocity impacts - Sfarra S. (FME Transactions, 2016)
In this work, the use of advanced thermographic techniques for the post-impact defect detection in basalt fibre reinforced composite laminates was investigated. The laminates were previously impacted at different energies, namely 7.5, 15 and 22.5 J and then subjected to accelerated environmental aging or to a coating process in order to conceal the previous damage due to low velocity impact. In both cases the defects could be identified using infrared thermography in the mid-wave infrared (MWIR) spectrum even after the treatments. In addition, short-wave infrared (SWIR) results were employed with the aim to clearly identify unsuspected resin-rich areas. Therefore, the non-thermal part of the infrared spectrum (SWIR) can be coupled with the thermal part (MWIR) providing a complete infrared vision beyond what is perceptible to the naked eye, i.e., in the visible spectrum.